Different inflammatory profile in young and elderly STEMI patients undergoing primary percutaneous coronary intervention (PPCI): Its influence on no-reflow and mortality. (1st September 2019) - Del Turco, Serena; Basta, Giuseppina; De Caterina, Alberto Ranieri; Sbrana, Silverio; Paradossi, Umberto; Taddei, Alessandro; Trianni, Giuseppe; Ravani, Marcello; Palmieri, Cataldo; Berti, Sergio; Mazzone, Annamaria
Abstract: Background: Coronary no-reflow phenomenon in ST-segment elevation myocardial infarction (STEMI) is associated with a poor clinical prognosis. Although its pathophysiology is not fully elucidated, a deregulated systemic inflammatory response plays an important role. Specifically, the relationship between age-associated differences in inflammatory markers and either no-reflow or mortality in STEMI patients undergoing primary percutaneous coronary intervention (pPCI) has never been investigated. Methods and results: We retrospectively enrolled 625 consecutive STEMI patients undergoing pPCI for whom a complete laboratory inflammatory pattern was available. Routinely blood measured laboratory parameters were collected at the moment of admission. No reflow was defined as Thrombolysis in Myocardial Infarction (TIMI) flow-grade lower than 3. The population was divided into two groups using a cut-off centered at 65 years. Compared to younger patients, elderly patients had higher mean values of fibrinogen, brain natriuretic peptide (BNP), leukocytes, neutrophil-to-lymphocyte ratio (NLR), C reactive protein/albumin ratio (CAR). Conversely, lymphocyte count and albumin levels were higher in young patients. In elderly patients, the values of NLR, CAR as well as leukocytes, fibrinogen and neutrophils were associated with no-reflow, while in young patients only BNP value was associated. At multivariate Cox regression analysis, only BNP and NLR resulted as independent predictors of all-cause mortality in the whole population and in elderly patients. Conclusions: Elderly STEMI patients on admission had a higher acute pro-inflammatory profile than young patients, associated to coronary no-reflow and mortality outcome. These results suggest that a different therapeutic approach between elderly and young STEMI patients should be agreed. Highlights: A deregulated inflammatory response plays a role in no-reflow in ST-segment elevation myocardial infarction (STEMI). Elderly STEMI patients on admission had a higher acute pro-inflammatory profile than young patients. This pro-inflammatory profile is associated to coronary no-reflow and mortality outcome. These results suggest that a different therapeutic approach between elderly and young STEMI patients should be agreed.